ANALYSIS OF GRATITUDE FOR PARENTS FOLLOWING THERAVĀDA BUDDHISM (Journal of Pharmaceutical Negative Results, 2023)
As the unclear bound of kindness in Buddhist doctrines led to the continuous issues about the repayment for parents and patrons. Although Tripitaka has already guided to repay, some cultures apply it ineffectively that led to the social problems. As the solutions, understanding the core of gratitude and applying with the other dharma principles likes the middle path. Gratitude is related to family roles, the parents looking after the children, the children repay with the gratitude. The gratitude main target is representing love and relation between parents or patrons and child. This is important for all community.